STRATEGI PENGEMBANGAN INDUSTRI KERAJINAN TAS NOKEN (STUDI KASUS PENGRAJIN LOKAL KABUPATEN MIMIKA) - Arief S. Zonggonau; Yuyun P. Rahayu; Marcus R. Maspaitella (Jurnal Ilmu Ekonomi, 2021)
This study examines the strategy for developing the Noken Bag Handicraft Industry (Case Study of Local Communities in Mimika Regency) by using three indicators: capital, raw materials, and marketing. Business owners or Noken artisans at the research location are the samples of this study gathered by the census method. Data retrieval used primary data and secondary data. Primary data obtained through questionnaires, and secondary data obtained through agencies and institutions related to this research. In addition, the analytical methods and tools used are descriptive statistical analysis and SWOT analysis. The results of this study are the formulation of a strategy for developing the Noken bag craft industry includes two approaches, precisely a method based on internal-external matrix analysis and a combination of SWOT matrix strategies. First, based on the SWOT internal-external matrix, the results show that the Noken bag craft industry in cell V is said to be in a position of concentration strategy through horizontal integration. Secondly, based on the SWOT matrix, the priority strategy that the Noken bag craft industry should apply is the SO strategy, which is a strategy that uses strength to take advantage of opportunities seen through three indicators, specifically capital, raw materials, and marketing.